2016
DOI: 10.1097/mlr.0000000000000495
|View full text |Cite
|
Sign up to set email alerts
|

Mammography Use Among Medicare Beneficiaries After Elimination of Cost Sharing

Abstract: Background We examined mammography use before and after Medicare eliminated cost sharing for screening mammography in January 2011. Methods Using National Health Interview Survey data, we examined changes in mammography use between 2010 and 2013 among Medicare beneficiaries aged 65–74 years. Logistic regression and predictive margins were used to examine changes in use after adjusting for covariates. Results In 2013, 74.7% of women reported a mammogram within 2 years, a 3.5 percentage point increase (95% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
1
23
0
1
Order By: Relevance
“…Consistent with other studies, we found that adults aged 65 and older with Medicare and public insurance or Medicare, no supplemental insurance have lower screening rates than individual with Medicare and private insurance (Klabunde et al, 2011; Sabatino et al, 2016). However, in multivariable adjusted analyses, only differences between Medicare and private insurance and Medicare, no supplemental insurance were statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other studies, we found that adults aged 65 and older with Medicare and public insurance or Medicare, no supplemental insurance have lower screening rates than individual with Medicare and private insurance (Klabunde et al, 2011; Sabatino et al, 2016). However, in multivariable adjusted analyses, only differences between Medicare and private insurance and Medicare, no supplemental insurance were statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…The differences in stages at diagnosis are essentially due to disparities in health services availability, a highly prevalent situation in Latin America and other developing countries, but also already reported in the USA 15,16 , Europe 6,17 and other countries of the world. In fact, an analysis of GLOBOCAN statistics has been conducted, demonstrating that breast cancer-related mortality is directly associated with the Human Development Index 18 , with one of the reasons being late detection, aggravated by unavailability of best treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there is evidence from multiple studies of increases in screening in the Medicare population after the ACA was implemented. 14,16,1821 Further, a recent study considering changes in early stage diagnoses of cancer among Medicare-aged individuals compared to younger cohorts and found a significant increase in early-stage colorectal cancer diagnoses (and decrease in late-stage diagnoses among men) though no evidence of changes in breast cancer stage. 22 …”
Section: Resultsmentioning
confidence: 99%
“…20 Another study found that among women with Medicare, there was a modest increase in mammography screening after the elimination of cost-sharing. 21 Notably, none of the studies considering the impact of cost-sharing elimination for Medicare beneficiaries were able to compare changes in screening to a valid control group, limiting the ability to draw robust conclusions regarding causality. Nonetheless, there is evidence from multiple studies of increases in screening in the Medicare population after the ACA was implemented.…”
Section: Resultsmentioning
confidence: 99%